Exploration of the Influencing Factors of Intelligent Robots on College Network Education in the All-Media Era - Chu, Na; Ma, Wanzhi (Journal of Engineering and Technological Sciences, 2024)
Online public opinion incidents in universities occur from time to time, with the source difficult to find, rapid dissemination, and escalating fragmentation. There are many problems and difficulties in the guidance of online public opinion in universities, and a new way out needs to be explored. This article explores the influencing factors of intelligent robots on online education in universities in the all-media era. This article believes that the ecology of university online education is an inherent component of university online culture and is the result of the interaction and mutual restraint between various elements and external environmental factors. The self-regulation of each element gradually tends towards a harmonious and stable state. It is closely related to cultural ecology, network cultural ecology, and university network culture, and also has its own unique characteristics. Establish a collaborative governance model between university public opinion work alliances and society, improve the application standards of artificial intelligence and the management mechanism of IGM and MGC technologies. Compared with traditional technologies, intelligent robots in the all-media era can guide the network public opinion of colleges and universities in the intelligent Internet era.